Aggressive course of atherosclerosis in hyperlipoproteinemia (a): a case series - A. M. Namitokov; V. K, Zaphiraki; E. K. Donets; O. B. Malyarevskaya; K. V. Karabakhtsieva; A. N. Yahutl (Столичная издательская компания, 2023)
Currently, worldwide interest in lipoprotein(a) (LP(a) as one of the most important markers of premature and aggressive atherosclerosis is steadily growing. This trend is due to both the new data on the pathogenesis of hyperlipoproteinemia (a) and the development of novel treatment methods in the near future. The variety of clinical manifestations of atherosclerosis associated with high LP(a) concentrations leads such patients to specialists of various profiles. The aim of this paper was to demonstrate, using examples from the practice of two lipid centers in Krasnodar, the diversity of clinical scenarios of atherosclerosis as a systemic disease in patients with very high LP(a) levels, as well as to highlight the current and future options for the treatment of hyperlipoproteinemia (a).